PENGARUH GREEN MARKETING, BRAND AWARENESS TERHADAP PURCHASE INTENTION AIR MINUM DALAM KEMASAN MEREK ADES MELALUI ENVIRONMENT ATTITUDE MAHASISWA PRODI MANAJEMEN UNIVERSITAS NIAS - Yupiter Mendrofa; Emanuel Zebua; Nov Elhan Gea; Yuterlin Zalukhu (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study was to analyze the effect of Green Marketing and Brand Awareness on Purchase Intention through the Environment Attitude of students of Management Study Program-S1, University of Nias. The appropriate analysis technique used is a structural equation model (SEM) based on variance or partial least squares (PLS) with smartPLS 4.0 software. Respondents to this study were 99 students of the Management Study Program-S1 Nias University TA.2020/2021 who were determined using the simple random sampling method. The stages of data testing are validity test, reliability test, termination coefficient test and hypothesis test. Based on the results of data analysis and research discussion, it can be concluded that Green Marketing has a significant influence on Environment Attitude, Brand Awareness has a significant influence on Environment Attitude, Green Marketing has no significant influence on Purchase intention, Brand Awareness has a significant influence on Purchase intention, Environment Attitude does not have a significant effect on Purchase intention, Brand Awareness has a significant influence on Purchase intention through Environment Attitude and Green Marketing does not have a significant effect on Purchase intention through Environment Attitude.